2021
DOI: 10.3390/ijms22147331
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteins Presenting Galactose and N-Acetylgalactosamine in Human Seminal Plasma as Potential Players Involved in Immune Modulation in the Fertilization Process

Abstract: In light of recent research, there is increasing evidence showing that extracellular semen components have a significant impact on the immune reaction of the female partner, leading to the tolerogenic response enabling the embryo development and implantation as well as further progress of healthy pregnancy. Seminal plasma glycoproteins are rich in the unique immunomodulatory glycoepitopes that may serve as ligands for endogenous lectins that decorate the surface of immune cells. Such interaction may be involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 87 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, the current study shows that galactose metabolism in F4 was significantly higher than that in F0 and Duroc; this might be also related to the significantly enriched Lactobacillus and Bifidobacterium in F4. Numerous studies reported that both Lactobacillus and Bifidobacterium could ferment lactose into galactose ( de Vries and Stouthamer, 1968 ; Turner and Martley, 1983 ; Hickey et al, 1986 ), which is involved in several physiological functions, such as protecting the intestinal epithelial barrier and improving immune function ( Salkovic-Petrisic, 2021 ; Szczykutowicz et al, 2021 ). Among them, Galacto-Oligo Saccharides (GOS) could also promote the proliferation of Lactobacillus and Bifidobacterium as well as the production of lactic acid and butyric acid ( Dai et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the current study shows that galactose metabolism in F4 was significantly higher than that in F0 and Duroc; this might be also related to the significantly enriched Lactobacillus and Bifidobacterium in F4. Numerous studies reported that both Lactobacillus and Bifidobacterium could ferment lactose into galactose ( de Vries and Stouthamer, 1968 ; Turner and Martley, 1983 ; Hickey et al, 1986 ), which is involved in several physiological functions, such as protecting the intestinal epithelial barrier and improving immune function ( Salkovic-Petrisic, 2021 ; Szczykutowicz et al, 2021 ). Among them, Galacto-Oligo Saccharides (GOS) could also promote the proliferation of Lactobacillus and Bifidobacterium as well as the production of lactic acid and butyric acid ( Dai et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study revealed the glycoproteins of seminal plasma, which are potential carriers of O-glycans terminated with Gal and GalNAc residues, including T and Tn antigens [172]. As already mentioned, both T and its precursor Tn antigen are hidden in normal cells but selectively exposed on cancer cells [87].…”
Section: Mgl Interactions-relevant For Fertilization and Pregnancy?mentioning
confidence: 83%
“…The presence of these glycoepitopes on identified glycoproteins makes them candidates for ligands of endogenous galactose-specific lectins, such as galectins or MGL. As potential carriers of GalNActerminated glycans, which are preferred by the MGL receptor, our analysis indicated prolactin-inducible protein (PIP), semenogelin-1 (SEMG1), semenogelin-2 SEMG2, lactotransferrin (LTF), prostate-specific antigen (KLK3), and fibronectin (FN1) [172].…”
Section: Mgl Interactions-relevant For Fertilization and Pregnancy?mentioning
confidence: 97%
“…Innate immunity plays an important role in human health [ 1 ]. During infection, injury, and disease conditions, the metabolism or nutritional homeostasis of the body is disturbed, involving various signaling pathways and secondary messenger molecules [ 2 , 3 ]. Innate immune responses protect our body through various alterations such as modulating membrane composition, antioxidants or cellular redox levels, and cytokines production [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%